Incidence of new-onset atrial fibrillation after cavotricuspid isthmus ablation for isolated typical atrial flutter: a systematic review and meta-analysis. (24th May 2021) - Griffin, A; Thiyagarajah, A; Middeldorp, M; Lau, D; Sanders, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: There is a lack of consensus guidelines regarding the continuation of anticoagulant therapy following cavotricuspid isthmus (CTI) ablation for typical atrial flutter. This is despite a significant number of patients developing new-onset atrial fibrillation (AF) following the procedure. Furthermore, a summary of Kaplan-Meier estimates for drug-free, arrhythmia-free survival has never been reported. Purpose: To estimate the incidence of drug-free, new-onset AF stratified by rhythm monitoring strategy in patients undergoing CTI ablation for isolated typical atrial flutter. Methods: PubMed, Embase and MEDLINE databases were searched to identify relevant studies. Only studies where anti-arrhythmic drugs were discontinued post-ablation and that accounted for patient censoring by reporting results in the form of time to event data were included. Data was extracted from published Kaplan-Meier curves using a digitizing software and confidence intervals for the survivor function were estimated based on the number at risk at the time point of interest. Results were pooled in a random effects model using the DerSimonian-Laird estimator. Results: Thirteen relevant studies incorporating 1712 patients (79 % male, mean age 63.2 +/-11.2 years, LVEF 55.2 +/-10.8%) were identified. The estimated freedom from new-onset atrial fibrillation was 89.7% (95% CI: 80.3-90.1%) at 1 year and 86.2% (95% CI: 78.4-94.0%) at 2 years in patients undergoing predominantly symptom –based monitoring, 74.6% (95%CI: 67.0-82.3%) at 1 year and 69.5% (95%CI: 63.5-75.6%) at 2 years in patients undergoing regular clinic follow-up with periodic Holter monitoring and 51.4% (95% CI: 41.8-61.0%) at 1 year and 22.7% (95% CI: 8.7% - 36.6%) at 2 years in patients with implantable loop recorders. Conclusion: With the advent of implantable loop recorders, it is apparent that most patients with isolated atrial flutter manifest new-onset AF following CTI ablation and the merits of discontinuing anticoagulation must be carefully considered in this population. Symptom-based monitoring likely severely underestimates the incidence of new-onset AF and may lead to adverse outcomes, particularly in patients with a high risk of stroke.